ANALISIS PENGARUH KETERSEDIAAN AIR BERSIH TERHADAP PRODUKTIVITAS USAHA PERTANIAN - Nisfi Medina; Rosalina Kumalati (Pelantar Press, 2024)
Clean water is an important factor in supporting the success of agricultural businesses. This study aims to analyze the effect of clean water availability on agricultural productivity using the library research method. Data were obtained from journals, books, research reports, and relevant official documents. The results of the study show that sufficient water availability has a positive effect on crop productivity, while water shortages cause a 30% decline in crop yields. In addition to quantity, water quality also plays an important role; high salinity has been shown to inhibit growth and reduce soil fertility. Climate variability, particularly the El Niño phenomenon, exacerbates drought conditions and results in delayed planting seasons, reduced farmer income, and risks to food security. Therefore, water resource management through improved irrigation infrastructure, the use of water-saving technologies, and environmental conservation are strategic steps to maintain agricultural productivity while supporting farmer welfare.